2017
DOI: 10.1161/jaha.117.006595
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Rated Health Status and Risk of Ischemic Heart Disease in the China Kadoorie Biobank Study: A Population‐Based Cohort Study

Abstract: BackgroundSelf‐rated health (SRH) is a strong predictor of mortality in different populations. However, the associations between SRH measures and risk of ischemic heart disease (IHD) have not been extensively explored, especially in a Chinese population.Methods and ResultsMore than 500 000 adults from 10 cities in China were followed from baseline (2004–2008) through December 31, 2013. Global and age‐comparative SRH were reported from baseline questionnaires. Incident IHD cases were identified through links to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…First, similar to prior studies, our analysis showed that SRH is associated with incident CVD events and all-cause mortality. 6 , 7 , 8 However, our study extends prior knowledge by examining, for the first time, the predictive value of SRH in the context of existing risk tools such as the PCE and CAC score, seeking to assess combinations of SRH, PCE, and CAC score that may improve current clinical risk assessment or provide quick and less expensive strategies for risk prediction in selective screening programs, population health management, research, or other settings where decisions are made based on risk. Importantly, SRH can easily be assessed electronically inside or outside the health care setting; therefore, its applicability is broad.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, similar to prior studies, our analysis showed that SRH is associated with incident CVD events and all-cause mortality. 6 , 7 , 8 However, our study extends prior knowledge by examining, for the first time, the predictive value of SRH in the context of existing risk tools such as the PCE and CAC score, seeking to assess combinations of SRH, PCE, and CAC score that may improve current clinical risk assessment or provide quick and less expensive strategies for risk prediction in selective screening programs, population health management, research, or other settings where decisions are made based on risk. Importantly, SRH can easily be assessed electronically inside or outside the health care setting; therefore, its applicability is broad.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants’ responses may be influenced by their educational status or prior interactions with the clinical environment. 7 Validation studies are therefore needed using similar simple measures of SRH across different populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The self-rated health, a construct that involves physical, mental and social aspects of life through the individual's general perception of their health [9], has been widely used in epidemiological studies, since it is a simple, subjective, easy-to-evaluate and applicable measure [10,11]. It is also used to compare health services, resource needs according to geographic areas, calculation of morbidity and mortality indicators [12][13][14] and functional decline [15,16].…”
mentioning
confidence: 99%